(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Peer review is the critical assessment of manuscripts submitted to scientific journals to facilitate ‘a fair hearing’ by experts in the field, to help authors and editors to improve the quality of reporting. It plays important role to ensure the integrity of research and publication, help maintain trust and ethical conduct of researcher and journal. By and large it is a quality control measure. Peer review starts with internal review for the suitability of manuscript to the journal, whether author have followed the guidelines. Normally two experts are sent the manuscript for review to see for the originality of work, study design, methodology, and relevance of the research. When both reviewers advise to accept, or reject the work, the decision is easier for the editor. When there are controversies, the editor may send for 3rd review. The final decision is solely that of the editor. Peer review is the basis of good science. Reviewing is a skill that requires to be developed. The reviewers are contacted by journal office, requesting their availability to complete the review within a certain time frame, usually 1-2 weeks. First abstract is sent to and if the reviewer agrees, the full manuscript is made available, either by email or by providing link to the online peer review system. The reviewers are required to declare any conflicts of interest to maintain ethics, keep the information confidential and do not publicly disclose or uses the information for personal gain. All comments regarding the review are communicated to the journal and not to the authors directly. The reviewers are requested for ‘constructive, concise and polite’ comments.